Development and validation of pharmaceutical care barriers scale in Chinese hospitals: a cross-sectional survey - Chen, Liangjiang; Yang, Nan; Huang, Yuankai; Xi, Xiaoyu (Frontiers in Pharmacology, 2023)
Background Chinese hospitals still face various barriers to implementing pharmaceutical care. The quantitative instrument for measuring these barriers in China is scarce. This study aims to develop and validate a scale for measuring barriers to providing pharmaceutical care in Chinese hospitals from the perspective of clinical pharmacists. Methods The scale was developed based on existing literature and qualitative interviews with 20 experts. The scale was included in a small-range pilot survey and then administered to a validation survey in 31 provinces in China. Exploratory factor analysis was used to identify the structure of the scale. Confirmatory factor analysis was applied to verify the structure of the scale and to validate the scale's convergent and discriminative validity. Known-group validity was also examined. Cronbach's alpha examined the internal consistency reliability of the scale. Results 292 scales were completed and returned for a response rate of 85.6% in the pilot study. Exploratory factor analysis of the scale suggested a five-factor solution (Cognition and attitude, Knowledge and skills, Objective conditions, External cooperation, and Support from managers) accounting for 66.03% of the total variance. 443 scales were sent out in the validation study, with a response rate of 81.0%. Confirmatory factor analysis demonstrated a good fit of the structural model for pharmaceutical care barriers. It showed the scale's good convergent and discriminative validity (The average variance extracted > 0.5 and composite reliability > 0.7). The scale could also identify the differences in total score among the clinical pharmacists from different hospital grades (p < 0.05). Cronbach's alpha is between 0.658 to 0.896, indicating good internal consistency. Conclusion From the perspective of clinical pharmacists, this study has developed a scale to assess obstacles to pharmaceutical care. The scale comprehensively encompasses barriers related to clinical pharmacists' cognitive and ability-related aspects, hindrances encountered in collaborating with other health professionals and patients, and barriers linked to the working environment. The reliability and validity have been established through verification.